Development of Raptor Model (Regular Ambulator Treatment Origination) Towards Physical Immobility of Stroke Patients With NIC and NOC Approach - Bayu Azhar; Gita Adelia; Candra Saputra; Nina Trisnawati; Wahyudi Wahyudi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Physical complaints of cancer patients can cause a decrease in physical well-being. Therefore, it is necessary to develop independent nursing therapy to overcome these problems, including oncology massage. The purpose of this study was to test the effectiveness of a new technique of oncology massage, a combination of effluerage and acupressure methods to improve physical well-being. This research method used randomized control trial, pre and post study method, single blind. The population was cancer patients treated at Dr. Adhyatma Hospital, with a sample of 44 respondents. This study was conducted for 6 months starting from June to November 2024. Data collection tools used BPI, PMS, BFI and PSQI. Data analysis used the t-test. The results showed a significant difference in physical well-being (p<0.05) on day-1 compared to day-5 in the intervention and control groups. There was a significant difference in physical well-being (p=0.041), including indicators: pain (p=0.014), physical fatigue (p=0.033), and quality of sleep (p=0.024), on day 5 after being given a new technique of oncology massage in the intervention group compared to the control, but there was no difference in physical mobility (p=0.325). The conclusion is new technique of oncology massage is effective in improving the physical well-being of cancer patients, especially reducing pain and physical fatigue and improving the quality of sleep. Suggestions are recommended that this new technique can be used as a nursing modality therapy in cancer patient care in hospitals.